Addressing the low students’ cognitive learning outcomes in Biology using CTL model: A case from SMA N 14 Kota Jambi - Simatupang, Santo V; Wicaksana, Ervan Johan; Natalia, Desfaur (Universitas Ahmad Dahlan, 2026)
Education plays an important role in developing students’ thinking abilities as reflected in their learning outcomes. This research aims to examine the effect of the contextual teaching and learning (CTL) model on the students’ cognitive learning outcomes, which refer to conceptual understanding and cognitive thinking skills across Bloom’s taxonomy levels. This research employed a quasi-experimental design using a non-randomized control group pretest–posttest design. We involved two groups of senior high school students, each consisted of 30 students. The experiment group was taught using the CTL model, while the control group was taught using the problem-based learning (PBL) model. Data were collected through pretest and posttest instruments. The results showed that the experimental class achieved a higher mean posttest score (55.24) than the control class (36.27). One-Way ANCOVA analysis indicated that the CTL model had a significant effect in improving the students’ cognitive learning outcomes in Biology.